A Child's Last Hours'Multidisciplinary Training in End-of-Life Care in Children's Hospitals: Adolescent With Cystic Fibrosis - Terry Murphy; D'Anna Saul; Elizabeth Hollenkamp; Matthew Niedner; James Azim; Adam Marks; Cecilia Trudeau; Katie Lehmann; Maureen Giacomazza; Patricia Keefer; Ken Pituch (Association of American Medical Colleges, 2016)
Abstract Introduction This resource is one of a three-module workshop using a case-based approach to teach interprofessional learners about end-of-life (EOL) care in dying hospitalized patients. This module is specific to an adolescent with end-stage cystic fibrosis and how to approach hospital-based care for this dying child and her family, encompassing symptom management and anticipatory EOL guidance to performing a death exam and debriefing. Methods The module includes video, questions/answers, and a pocket card. Ideally, the group of learners should consist of seven to 10 learners from a multidisciplinary background including but not limited to nurses, physicians, social worker, spiritual care providers, and respiratory therapists. The ideal team for moderating this workshop includes 2-3 individuals, preferably with differing professional backgrounds, who have comfort and familiarity with pediatric EOL. Results At our institution, from 2010-2013, we presented our workshop to over 200 nurses, medical students, house officers, fellows, respiratory therapists, social workers, and spiritual care providers. Participants completed a 16-item retrospective posttest to assess confidence in knowledge and skill domains important in caring for dying children. Eighty-six percent of those surveyed agreed or strongly agreed that the workshop "helped me participate more effectively in the care of the patient as (s)he neared death." Eighty-six percent also felt that the workshop "reduced the anxiety or stress I would otherwise have experienced in caring for the patient as (s)he neared death." Discussion This workshop has been refined over the past five years of implementation to reflect this current module. Our evaluation shows a clear improvement in confidence corresponding with the workshop, and data following inpatient deaths suggest that the workshop is applicable in the clinical realm. To the authors' knowledge, it is the first structured workshop of its kind to address pediatric EOL care.